A STUDY OF NON-VERBAL COMMUNICATION IN HOSPITALS AND ITS INFLUENCE IN THE RECOVERY OF PATIENTS - P. Ravi; Vethabothagam, Haebus Solomon (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This descriptive research study examines the impact of non-verbal communication on patient recovery outcomes in hospital settings. Non-verbal communication, encompassing body language, facial expressions, eye contact, touch, spatial relationships, and environmental factors, plays a crucial role in healthcare delivery and patient experience. This study employed a descriptive research design with a sample of 400 respondents, including patients, healthcare professionals, and family members across multiple hospital departments. Data was collected through structured questionnaires, observational checklists, and patient recovery metrics over a six-month period. The findings reveal a significant positive correlation between effective non-verbal communication practices and improved patient recovery rates, reduced anxiety levels, enhanced patient satisfaction, and shorter hospital stays. Healthcare professionals who demonstrated empathetic non-verbal behaviors, maintained appropriate eye contact, and used therapeutic touch appropriately showed measurably better patient outcomes. The study recommends implementing comprehensive non-verbal communication training programs for healthcare staff, establishing standardized protocols for therapeutic communication, and creating healing environments that support positive non-verbal interactions. These findings contribute to the growing body of evidence supporting the integration of communication skills training in healthcare education and practice.